Learn Blackberry Games Development - Hamer, Carol; Davison, Andrew; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
BlackBerry smart phones aren$1 (Bt just for business. In fact, throw away that boring spreadsheet, tear up that yearly budget report$1 (Bthe BlackBerry is a lean, mean game-playing machine. Carol Hamer and Andrew Davison, expert software game developers, show you how to leverage the BlackBerry Java$1!" (BDevelopment Environment (based on Java ME) to design and create fun, sophisticated game applications from role playing to dueling with light sabers. The BlackBerry: not as clumsy or as random as a blaster$1 (Ban elegant device, for a more civilized age. In this book, Carol and Andrew give you the professional techniques you need to use music, 2D and 3D graphics, maps, and game design patterns to build peer-to-peer games, role playing games, and more for the BlackBerry.s
Gaming on BlackBerry -- BlackBerry Application Basics -- Game Graphics and Events with MIDP and RIM Classes -- Adding a Professional Look and Feel -- Security and Selling Your Game -- Swingin$1 (BLight Saber -- Play a Live Opponent with SMS -- Using Scalable Vector Graphics -- Creating Role-Playing Games on the Internet -- Remotely Drive a (Toy) Sports Car -- Fox and Hounds -- Introducing 3D with JSR 239.s
Keywords: Computer science; Computer Science; Programming Techniques